Acute Kidney Injury in Patients with Acute Type B Aortic Dissection. (February 2023) - Musajee, Mustafa; Katsogridakis, Emmanuel; Kiberu, Yusuf; Banerjee, Christopher; George, Rhys; Modarai, Bijan; Saratzis, Athanasios; Sandford, Becky
Abstract : Objective: Acute kidney injury (AKI) is common in patients with aortic diseases; however, it has not been extensively studied in acute type B aortic dissection (TBAD). AKI is known to be associated with adverse kidney outcomes and premature death. This study investigated the incidence and impact of AKI in patients with acute TBAD. Methods: This was a retrospective study including data from two tertiary vascular centres in the UK. Case notes and electronic records were reviewed for consecutive patients presenting with acute symptomatic TBAD. Patients were managed according to a uniform clinical protocol; both patients who underwent surgery and those managed conservatively were included in this analysis. Serum creatinine values were used to calculate the number of patients who developed AKI, based on validated Kidney Disease Improving Global Outcomes definitions. Associations between incidence of AKI, death, and Major Adverse Kidney Events (MAKE; defined as death, dialysis and/or drop in estimated glomerular filtration rate > 25%) were explored. Results: Overall, 66 (42.6%) of 155 patients developed AKI within one week of presenting with TBAD. Of these, 23 patients (34.8%) had stage 1, 26 patients (39.4%) stage 2, and 17 patients (25.8%) stage 3 AKI. MAKE at 30 and 90 days occurred in 17 (11.0%) and 12 patients (7.7%), respectively. AKI was associated with significantly worse outcomes, with a 24.2% mortality rate in the AKI group compared with 7.8% among those with no AKI ( p <.001); this association was also significant in adjusted analyses, both in patients who did and did not undergo surgery. Conclusion: AKI is very common among patients presenting with acute TBAD, even in clinically uncomplicated disease. There was a significant association with mortality and MAKE, whether patients underwent surgery or not. This warrants further investigation to better understand the underlying causes of the AKI and investigate management strategies which may improve outcomes.